THE IMPORTANCE OF USING THE LAWS OF DRAWING IN TEACHING TECHNOLOGY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Integrating drawing principles into technology education offers a unique approach to developing students’ creativity, problem-solving skills, and visual communication. This article explores the importance of using drawing techniques and concepts in teaching technology subjects, highlighting their role in fostering innovation, design thinking, and effective communication in a technologically driven world.